Ultrasound Diagnosis of Placenta Previa and its Associated Risk Factors with Parity and Previous Cesarean Section: Placenta Previa and its Associated Risk Factors with Parity - Amir, Arshia; John, Akash; Ali, Abid; Fatima, Nayab; Bakhtawar, Khadija (Pakistan Journal of Health Sciences, 2022)
Placenta previa is a pregnancy condition in which the placenta is positioned abnormally either partially or completely covering the cervix. Females with prior cesarean section are at increased risk of developing placenta previa. Objective: To evaluate Placenta Previa and its Associated Risk Factors with Parity and Previous Cesarean Section using ultrasound. Methods: It was a cross-sectional study carried out at the private sector hospital of Gujranwala over 4 months period from December 2021 to March 2022. A total of 42 patients were selected using a convenient sampling approach. Patients identified with placenta previa following ultrasound examination were included after receiving informed consent. The patient’s demographic statistics were collected on a specially designed data collecting sheet. The data were analyzed using the SSPS V20.0. Results: The result of this study revealed that women in their 20-30 years are most affected. Most of the women 27(64.3%) with placenta previa present asymptomatic. Risk increases with an increased number of parity and prior cesarean section. Anterior location is the most prevalent location for placenta previa 20(47.6%). Conclusion: The ultrasound is fully capable of detecting placenta previa, its type, and location. There is a direct relationship between previous cesarean section and multiparity with the risk of developing placenta previa.